Rola klastrów kryzysowych w zwalczaniu katastrof naturalnych na przykładzie powiatu kamieńskiego - Piepiora, Zbigniew (The Meaning of the Crisis Clusters in the Prevention of the Natural Disasters in Kamień Pomorski District (NUTS-4), 2008)
This article describes the new concept of crisis clusters and their meaning in the prevention of natural disasters - the case study of Kamień Pomorski district (NUTS-4). Creating and functioning of the crisis clusters conduct (indirectly) to the increase of the competitiveness of the regions. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 53-60